PENGGUNAAN METODE PROBLEM BASED LEARNING BERBANTUAN LEMBAR KERJA SISWA (LKS) TERHADAP KEMAMPUAN BERPIKIR KRITIS - Mulyati, Sri (Promosi: Jurnal Program Studi Pendidikan Ekonomi, 2023)
The problem in this study is the low critical thinking skills of students. Some students are not used to high-level thinking (HoTS), some projects and assignment results are done by copying and pasting without any critical analysis. The purpose of this study was to describe the differences in students' critical thinking abilities between the experimental class using the PBL method and the control class using the conventional method. This type of research used is quantitative research with experimental methods. Data collection techniques with complex multiple choice tests. Statistical prerequisite tests carried out were the normality test and data homogeneity test, the hypothesis test was carried out by the t test and the gain test was carried out to see the increase. The results showed that there was a difference in increasing students' critical thinking skills between the experimental class using the PBL method and the control class using the conventional method. It can be seen from the gain value of the experimental class of 0.65 and that of the control class of 0.50. It can be concluded that the PBL method with the help of worksheets can be used as an alternative for educators to improve and develop students' critical thinking skills.Keywords: Critical Thinking; Problem Based Learning; Student Worksheet